KEPUTUSAN PEMBELIAN KONSUMEN MAKANAN PRODUK HALAL (Studi Kasus Pada Dominocake Di Wilayah Cibubur, Jakarta Timur) - Nanda Pratiwi (2020)
This research was conducted aiming to find out and analyze the effect of product quality and halal awareness on purchasing decisions. This type of research is a quantitative study and the population in this study are consumers who have made purchases and have consumed DominoCake at Cibubur, East Jakarta outlets with samples taken as much as 50 respondents. The sampling technique used in this study is non-probability sampling with a purposive sampling method, data collection is done through questionnaires. The data analysis technique used is the PLS (Partial Least Square) analysis method with SmartPLS 3.2 software. The results of this study indicate that (1) Product Quality does not significantly influence purchasing decisions. (2) Halal awareness has a significant effect on purchasing decisions.